PELATIHAN TOEFL UNTUK SISWA/SISWI KELAS XII DI SMAN 1 JAMBLANG KABUPATEN CIREBON - Deden Novan Setiawan Nugraha; Ervina CM Simatupang; Puspita Sari (Jurnal Abdimas Bina Bangsa, 2023)
This community service activity (PKM) was carried out to provide class XII students at SMAN 1, Jamblang, Cirebon Regency with an understanding and knowledge of the TOEFL. This is because many of the students do not know what TOEFL is, what is the importance of TOEFL, what are the forms of TOEFL, and what are the strategies for answering TOEFL questions. The methods used in this training are lectures, discussions, and exercises. The results of the activity showed that students in class XII at SMAN 1 Jamblang Cirebon Regency gained additional insight and knowledge about the TOEFL